Application of anticorrosive materials in cement slurry: Progress and prospect - Zhang, Yihang; Wen, Jiaxin; Yin, Xuejiao; Zhang, Xin (Frontiers in Materials, 2022)
In gas well-cementing operation, the acidic formation environment will seriously affect the engineering performance of cement slurry, such as the consolidation time and compressive strength. At the same time, the erosion of formation corrosive medium will also destroy the cementation between the cement paste and the well wall in the sealing section, reduce the mechanical properties of the cement paste, lead to problems such as well wall collapse and casing damage, seriously endanger the normal exploitation of oil and gas resources, and cause major safety accidents. Therefore, improving the corrosion resistance of cement paste is the key to ensure long-term stable cementing of ultra-high temperature sour gas wells. This paper summarizes the influencing factors, corrosion mechanism, corrosion test methods and research status of anti-corrosion oil well cement additives, discusses the advantages and disadvantages of each anti-corrosion additive, summarizes the latest progress and challenges of anti-corrosion oil well cement, and aims to provide some reference for researchers in related fields.